Investigation of Dependent Rikitake System to Initiation Point - Yousof Gholipour; Amin Ramezani; Mahmood Mola (Institute of Advanced Engineering and Science, 2015)
In this paper we investigate depending of the Rikitake system to initiation point, and monitor changing behavior of this system. We will have 4 initiation points in Cartesian system. We at 4 positions, will monitor behavior of this system, while holding constant other values, and after per position, will draw operation of system on axes of x, y, z and 3-D plot. We want to know, what is the effect of initiation point on Rikitake system? Numerical simulations to illustrate the effect of initiation point are presented, and at the end conclusions and comparing the states together are obtained.